Kinetics and equilibriums adsorption of Cu (II) ion by chitosan and cross-linked chitosan-bentonite - Hargono Hargono; Angga Mei Sarah; Feninda Nevrita; Bakti Jos (Dept. of Chemical Engineering, Diponegoro University, 2019)
The sorption of Cu (II) particle from aqueous solution onto chitosan and cross-connected chitosan-bentonite (CTS-BTN) as adsorbent were conducted in batch conditions. The impact of different test parameters: starting pH, sorption time was assessed. Equilibrium studies have been completed to decide the limit of chitosan and CTS-BTN for Cu (II) particle. The Langmuir and Freundlich isotherm models were used in the examination of the trial information as linearized conditions. It was discovered that the isotherm information were all around portrayed by the Langmuir isotherm. Chitosan and CTS-BTN showed an adsorption capacity of 125 mg/g and 142.86 mg/g, respectively. The constant of adsorption rate was investigation utilizing a pseudo first order and a pseudo second order model. The pseudo second order model brought about the best fit with test information (R2= 0,991 for CTS and R2= 0,995 for CTS-BTN), additionally giving a constant rate k2, ads= 8.85 x 10-5 g/mg min for CTS and 3.72 x 10-4 g/mg min for CTS-BTN. Recommending that this model could be used in design and applications.Keywords: adsorption; Cu(II) ion; chitosan; cross-linked; isotherm; kinetics